2010
DOI: 10.1017/s1049096510000740
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Productivity in Non-Ph.D. Departments

Abstract: Political scientists hail from large, research-intensive universities like the Ohio State University, regional comprehensive schools like Western Kentucky University, and small teaching-intensive institutions like Mars Hill College. Despite this diversity, most studies of the political science discipline overlook the contributions of individuals from non-Ph.D. departments. To address this oversight, we compare the publishing rates of scholars with four types of affiliations: non-Ph.D. departments, Ph.D. depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This last limitation is significant. In 2010, nearly 30 percent of the contributors to ASR were based in departments other than sociology (Kaba 2015), and a significant number of social science authors do not hold faculty appointments in academic departments (Collins, Cooper, and Knotts 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This last limitation is significant. In 2010, nearly 30 percent of the contributors to ASR were based in departments other than sociology (Kaba 2015), and a significant number of social science authors do not hold faculty appointments in academic departments (Collins, Cooper, and Knotts 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Across the disciplines, publishing productivity is strongly related to institution type (e.g., research university or liberal arts college) (Collins, Cooper, and Knotts 2010; Joy 2006; Nakhaie 2002; Stack 2004). As John W. Creswell (1985) has pointed out, this can be attributed to differences in resources, expectations, incentives, and opportunities for collaboration.…”
Section: Previous Researchmentioning
confidence: 99%
“…Editors want accomplished scholars to serve as associate editors and as board members, but they might also think more broadly about the types of scholars who could serve the journal well. For example, Collins et al (2010) found that political science faculty members at non-PhD-granting institutions represented 16% of authors in 26 political science journals between 2000 and 2007, but that in 2008 they composed just 9% of the editorial board members. While some men and women may not have published as many articles in as many prestigious journals because of higher teaching loads, university service, or family commitments, they could bring other skills and perspectives to editorial positions.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 provides an overview of the proportion of women in the profession at the assistant-, associate-, and full-professor ranks in political science in 2010. Because most editors and editorial board members are on the faculty at research universities (Collins et al 2010), we have also provided statistics on women at PhD-granting institutions. As the table shows, the overall proportions of women in the profession are similar to the proportions of women at PhD-granting institutions.…”
Section: The Relatively Good News: the Presence Of Women In Editorialmentioning
confidence: 99%